Environmental Toxins and Their Organ-Specific Effects: A Comprehensive Review of Human Exposure and Accumulation - Ibadi, Emam Atiyah; Awad, Hussein Kamil; Hussain, Lujain Ibrahim (Journal of agricultural, environmental and veterinary sciences, 2024)
Environmental pollutants lead to problems in ecosystems differently depending on the extent of their toxicity, and thus their arrival to humans leads to health problems at different levels. The danger of any substance introduced into the environment can be determined depending on its quantity (dose). In addition, based on the overdose, it can be considered (whether it is alien or original) is toxic. Poisoning is the harmful effect that occurs as a result of ingestion, inhalation, or contact with a toxic substance. Potential toxic substances include chemical, biological, and physical toxins, fungi, plants, and animal toxins. Environmental pollutants are heavy metals (lead, cadmium, mercury, etc.), pesticides, organic materials, food additives, etc. The severity of the toxic effect depends primarily on the concentration and persistence of the final toxic substance. The final toxic substance is often the original chemical to which the organism is exposed. In other cases, the final toxic substance is a metabolite of the original compound, reactive oxygen species, or nitrogen (ROS, RNS) generated during Transformation into a toxic substance. Exposure to lead can affect proteins that interfere with their enzymatic functions or ability to bind other cellular components, leading to DNA damage and induction of oxidative stress. Asbestos can also damage DNA and affect gene expression. Exposure to acrolein irritates the bronchi, while mercury causes neurological symptoms. This review deals with understanding toxic environmental pollutants that affect humans, the extent of accumulation of toxic substances in organs, and methods of exposure to them.